SEEP: Exploiting Symbolic Execution for Energy-Aware Programming - Hönig, Timo; Eibel, Christopher; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Proceedings of the 4th Workshop on Power-Aware Computing and Systems (HotPower 2011), 2011)
In recent years, there has been a rapid evolution of energy-aware computing systems (e.g., mobile devices, wireless sensor nodes), as still rising system complexity and increasing user demands make energy a permanently scarce resource. While static and dynamic optimizations for energy-aware execution have been massively explored, writing energy-efficient programs in the first place has only received limited attention. This paper proposes SEEP, a framework which exploits symbolic execution and platform-specific energy profiles to provide the basis for energy-aware programming. More specifically, the framework provides developers with information about the energy demand of their code at hand, even for the invocation of library functions and in settings with multiple possibly strongly heterogeneous target platforms. This equips developers with the necessary knowledge to take energy demand into account during the task of writing programs. © 2011 ACM.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.seepex